Emergence of Flucytosine-Resistant Candida tropicalis Clade, the Netherlands - Delma,FZ; Spruijtenburg,B; Meis,JF; de,Jong AW; Groot,J; Rhodes,J; Melchers,WJG; Verweij,PE; de,Groot T; Meijer,EFJ; Buil,JB (Emerging Infectious Diseases, 2025)
Candida tropicalis is the second most virulent Candida species after C. albicans. Previous studies from the Netherlands and France reported a notable reduction in susceptibility to flucytosine (5-FC) in a substantial proportion of C. tropicalis isolates. We investigated epidemiologic patterns of C. tropicalis isolates in the Netherlands and the genetic mechanisms driving widespread non–wild-type (WT) 5-FC resistance. We conducted antifungal susceptibility testing and used advanced molecular techniques, including short tandem repeat genotyping and whole-genome sequencing paired with single-nucleotide polymorphism analysis, to analyze 250 C. tropicalis isolates collected across the Netherlands during 2012–2022. Our findings revealed the rapid emergence of a 5-FC–resistant, non-WT C. tropicalis clade, accounting for >40% of all C. tropicalis isolates by 2022. Genomic analysis identified a homozygous nonsense mutation in the FCY2 gene, which was exclusive to this non-WT population. Continued surveillance efforts are needed to detect and prevent the spread of drug-resistant Candida species.